KARAKTERISTIK SYMPHYLID PADA TANAMAN NANAS (Ananas comosus (L.) Merr) DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - Mifyatul Jannah; Desita Salbiah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The aims of this research were to find out the type of symphylid that attacks pineapple plants in Kualu Nenas Village. The research was conducted in the pineapple garden of Kualu Nenas Village, Tambang District, Kampar Regency for taking of symphylid and Laboratory of Plant Pest, Faculty of Agriculture, University of Riau for identification of symphylid. The research was conducted from May 2017 to June 2017. Research using survey method. The location of the garden was determined using a purposive sampling method in pineapple gardens in Kualu Nenas Village, Tambang District, Kampar Regency. Determination of pineapple gardens is based on the widest land, which is obtained by three pineapple gardens with an area of 2000 m2, 1000 m2 and 600 m2. In each pineapple garden, several sample points were determined for bait trapping. The symphylid results obtained from identification in the laboratory were analyzed descriptively and presented in the form of tables and shapes of the images. The pineapple in Kualu Nenas availlage Tambang District Kampar Regency Riau Province including the Arthropoda phylum, Symphyla order, Scutigerellidae family, Hanseniella genus.